PRE-VISEAN FORAMINIFERS FROM CENTRAL ASIA AND KAZAKHSTAN - Sabirov A.A. (My University, 2004)
The data on the geological and geographical distribution of pre-Visean foraminifers in central Asia and Kazakhstan are generalized, foraminiferal assemblages of various age are characterized, and the most important points indicative of crucial moments in the evolution of this group are recognized.
Keywords: foraminifers; Paleozoic::Carboniferous::Mississippian::Middle::Visean; Палеозой::Каменноугольная::Средний::Визейский